Customized strategies for high-yield purification of retinal pigment epithelial cells differentiated from different stem cell sources - Regha, Kakkad (2023)
Retinal pigment epithelial (RPE) cell dysfunction and death are characteristics of age-related macular degeneration. A promising therapeutic option is RPE cell transplantation. Development of clinical grade stem-cell derived RPE requires efficient in vitro differentiation and purification methods. Enzymatic purification of RPE relies on the relative adherence of RPE and non-RPE cells to the culture plate. However, morphology and adherence of non-RPE cells differ for different stem cell sources. In cases whereby the non-RPE adhered as strongly as RPE cells to the culture plate, enzymatic method of purification is unsuitable. Thus, we hypothesized the need to customize purification strategies for RPE derived from different stem cell sources. We systematically compared five different RPE purification methods, including manual, enzymatic, flow cytometry-based sorting or combinations thereof for parameters including cell throughput, yield, purity and functionality. Flow cytometry-based approach was suitable for RPE isolation from heterogeneous cultures with highly adherent non-RPE cells, albeit with lower yield. Although all five purification methods generated pure and functional RPE, there were significant differences in yield and processing times. Based on the high purity of the resulting RPE and relatively short processing time, we conclude that a combination of enzymatic and manual purification is ideal for clinical applications.